Impact of Extended Lymph Node Dissection on Survival Outcomes in Patients With Bladder Cancer and Upper Tract Urothelial Carcinoma: A Multicenter Retrospective Study - Jiwoong Yu; Wook Nam; Kyung Hwan Kim; Yun-Sok Ha; Geehyun Song; Ho Kyung Seo; Jong Kil Nam; Tae Il Noh; Seok Ho Kang; Seung-Hwan Jeong; Ja Hyeon Ku; Jong Jin Oh; et al. (Journal of Urologic Oncology)
Purpose To evaluate whether extended pelvic lymph node dissection (PLND) improves survival outcomes compared with standard PLND in patients with bladder cancer (BCa) undergoing radical cystectomy (RC), and to assess its potential benefits in patients with prior or concurrent radical nephroureterectomy (p/cRNU). Materials and Methods A multicenter analysis included 2202 patients with BCa undergoing RC with standard or extended PLND at 11 tertiary centers from 2003 to 2023. Following propensity score matching, 659 pairs (n=1,318), including 128 patients with p/cRNU, were analyzed. Recurrence-free survival (RFS) was the primary outcome, while overall survival (OS), cancer-specific survival (CSS), and readmission rates were secondary outcomes. Survival analyses performed using Kaplan-Meier methods and clustered Cox models. Results Extended PLND yielded significantly more lymph nodes than standard PLND (median: 27.0 vs. 17.0, p<0.001) but did not improve RFS, CSS, or OS in the overall cohort (all p>0.05). Extended PLND increased readmission rates (28.4% vs. 20.2%, p=0.001) and readmission risk (odds ratio, 1.57; 95% confidence interval [CI], 1.15–2.16, p=0.005). However, subgroup analysis revealed extended PLND significantly improved RFS in patients with p/cRNU (hazard ratio, 0.54; 95% CI, 0.38–0.77; p<0.001). Conclusion Extended PLND does not provide survival benefits for overall patient population and increases readmission risk but significantly improves RFS in patients with p/cRNU. Tailoring PLND extent based on upper tract disease status is recommended.